Development of ARMS PCR tests for detection of common CFTR gene mutations - Soloviov, O.O.; Pampukha, V.M.; Livshits, L.A. (Вiopolymers and Cell, 2010)
Aim. To develop diagnostic assays, based on the amplification refractory mutation system (ARMS) principle, for detection of common mutations in the CFTR gene using two approaches: standard PCR with further gel-electrophoresis and Real-Time PCR with SYBR Green. Materials. For this study we have chosen the following mutations: dF508, W1282X, R117H, 621 + 1G > T, 2143delT with the frequencies in Ukraine: dF508 – 43.3 %; 2143delT – 1.38 %; W1282X – 1.1 %; R117H, 621 + 1G > T – < 0.6 %. For the development and validation of the assay we have used control DNA samples with abovementioned mutations, which were previously examined using RFLP and heteroduplex analysis. Results. We have designed the primers and optimized the conditions of ARMS PCR performing for the analysis of dF508, W1282X, R117H, 621 + 1G > T, 2143delT mutations. To validate the developed assays we have analyzed control DNA samples with the following mutations: W1282X (n = 3), R117H (n = 2), 621 + 1G > T (n = 1), 2143delT (n = 1). For validation of the dF508 assay we have analyzed 100 heterozygous carriers and 50 homozygous carriers. We have analyzed 48 patients with cystic fibrosis, in which only one mutation was previously detected in combination with unknown mutant variant, using the developed ARMS assay for the 2143delT mutation, and detected 4 heterozygous carriers. No differences were observed in comparison with the standard protocols. Conclusions. It was shown that ARMS is a reliable, rapid and inexpensive method, and the developed assays can be applied in the standard PCR protocol with further gel-electrophoresis as well as using Real-Time PCR with SYBR Green for the molecular genetic diagnostics of cystic fibrosis. Мета. Мета дослідження полягала у розробці діагностичних методик, основаних на принципі алель-специфічної ПЛР для аналізу розповсюджених мутацій в гені ТРБМ з використанням двох підходів: традиційної ПЛР з подальшим розділенням продуктів у гель-електрофорезі та з використанням ПЛР у реальному часі. Методи. Для дослідження обрано такі мутації – dF508, W1282X, R117H, 621 + 1G > T, 2143delT з частотою зустрічальності в Україні: dF508 – 43,3 %; 2143delT – 1,38 %; W1282X – 1,1 %; R117H і 621 + 1G > T – < 0,6 %. Використано контрольні зразки ДНК з відповідними мутаціями, ідентифіковані методами гетеродуплексного аналізу та ПДРФ. Результати. Проведено дизайн та оптимізовано умови алель-специфічної ампліфікації для вивчення мутацій dF508, W1282X, R117H, 621 + 1G > T, 2143delT. Розроблені методики аналізу підтверджено перевіркою контрольних зразків ДНК з мутаціями W1282X (n = 3), R117H (n = 2), 621 + 1G > T (n = 1), 2143delT (n = 1). Щоб перевірити тест на dF508 нами проаналізовано 100 носіїв даної мутації в гетерозиготному стані та 50 – в гомозиготному. За допомогою створеної методики детекції 2143delT проаналізовано також 48 пацієнтів, хворих на муковісцидоз, у яких первинно виявлено лише по одній мутації разом з невідомим мутантним варіантом. В результаті аналізу серед них визначено ще чотири носії зазначеної делеції в гетерозиготному стані. При цьому не встановлено розбіжностей в даних, отриманих з використанням стандартних протоколів аналізу досліджених мутацій. Висновки. Показано, що метод алель-специфічної ПЛР є швидким та відносно недорогим, його можна застосовувати для детекції відомих мутацій у гені ТРБМ. Цель работы состояла в разработке диагностических методик, основанных на принципе аллель-специфической ПЦР для анализа распространенных мутаций в гене ТРБМ с использованием двух подходов: традиционной ПЦР c дальнейшим разделением продуктов в гель-электрофорезе и ПЦР в реальном времени. Методы. Для исследований выбраны следующие мутации – dF508, W1282X, R117H, 621 + 1G > T, 2143delT с частотой встречаемости в Украине: dF508 – 43,3 %; 2143delT – 1,38 %; W1282X – 1,1 %; R117H и 621 + 1G > T – < 0,6 %. Использованы контрольные образцы ДНК с соответствующими мутациями, идентифицированные методами гетеродуплексного анализа и ПДРФ-анализа. Результаты. Проведен дизайн и оптимизированы условия аллель-специфической амплификации для анализа мутаций dF508, W1282X, R117H, 621 + 1G > T, 2143delT. Разработанные методики анализа подтверждены проверкой контрольных образцов ДНК с мутациями W1282X (n = 3), R117H (n = 2), 621 + 1G > T (n = 1), 2143delT (n = 1). Для проверки теста на dF508 проанализированы 100 носителей данной мутации в гетерозиготном состоянии и 50 – в гомозиготном состоянии. С помощью разработанной методики детекции 2143delT проанализированы также 48 пациентов, больных муковисцидозом, у которых первично выявлено лишь по одной мутации вместе с неизвестным мутантным вариантом. В результате анализа среди них определены еще четырее носителя указанной делеции в гетерозиготном состоянии. При этом не найдено отличий в данных, полученных с использованием стандартных протоколов анализа этих мутаций. Выводы. Показано, что метод аллель-специфической ПЦР является быстрым и относительно недорогим, его можно применять для детекции известных мутаций в гене ТРБМ.